Analysis of The Effect of On-Time Performance, Safety, Comfort, And Accessibility on E-WOM Through Passenger Satisfaction at Cililitan Terminal - Nur Prasetyo; Dian Artanti Arubusman; Rully Indrawan; Djamal Subastian; Edi Abdurachman (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study investigates the effects of on-time performance, safety, comfort, and accessibility on electronic Word of Mouth (e-WOM) through passenger satisfaction at Cililitan Bus Terminal. Using a quantitative approach, data were collected from 270 respondents through a structured questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that on-time performance, comfort, and accessibility significantly influence passenger satisfaction, while safety does not. Furthermore, on-time performance and comfort have a direct and significant impact on e-WOM, whereas safety and accessibility do not. Passenger satisfaction serves as a mediating variable, strengthening the relationship between service quality factors and e-WOM. These findings highlight the importance of punctuality, comfort, and ease of access in enhancing passenger experience and fostering loyalty through positive word of mouth. Terminal operators are encouraged to focus on improving these aspects to ensure sustainable service quality and customer engagement.